Embodied prototyping: exploration of a design-fabrication framework for large-scale model manufacturing. Issue 1 (2nd January 2016) - Sass, Lawrence; Chen, Lujie; Sung, Woong Ki
ABSTRACT: For designers of large products such as boats, cars and houses, there have been few cost-effective machines or methods in support of one-to-one, large-scale physical prototyping. A novel physical production system is demonstrated, aiming at rapid prototyping of large-scale models. Research questions address possible ways that the system can support design prototyping as opposed to manufacturing. We present computational methods used to generate model data, principle of decomposition of a large model, and assembly of components to form 3D prototypes. The process of model making in this study revealed an extended use of human body. Our view on embodied cognition in relation to the development of the large-scale rapid prototyping system is discussed. We end with a projection of new possibilities for large-scale prototyping that engages the human body. GRAPHICAL ABSTRACT: